2003
DOI: 10.1111/j.1464-5491.2003.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Grading and disease management in national screening for diabetic retinopathy in England and Wales

Abstract: The protocol developed by the Diabetic Retinopathy Grading and Disease Management Working Party represents a new consensus upon which national guidelines can be based leading to the introduction of quality-assured screening for people with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
164
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(168 citation statements)
references
References 14 publications
0
164
1
1
Order By: Relevance
“…The criteria used for grading and allocation of R and M levels are those required by the English NHS Diabetic Eye Screening Programme 8 and the relationship to the Early Treatment Diabetic Retinopathy Study (ETDRS) severity scale 9, 10 are shown in Table 1. Referable diabetic retinopathy was defined in the English programmes by the presence of any of R2 (moderate to severe non‐proliferative diabetic retinopathy), R3 (proliferative diabetic retinopathy) or M1 (maculopathy) in at least one eye and the equivalent levels were identified in the Scottish screening programme.…”
Section: Methodsmentioning
confidence: 99%
“…The criteria used for grading and allocation of R and M levels are those required by the English NHS Diabetic Eye Screening Programme 8 and the relationship to the Early Treatment Diabetic Retinopathy Study (ETDRS) severity scale 9, 10 are shown in Table 1. Referable diabetic retinopathy was defined in the English programmes by the presence of any of R2 (moderate to severe non‐proliferative diabetic retinopathy), R3 (proliferative diabetic retinopathy) or M1 (maculopathy) in at least one eye and the equivalent levels were identified in the Scottish screening programme.…”
Section: Methodsmentioning
confidence: 99%
“…A digital fundus camera was used to take two 45°images (one macula-centred and one optic disc-centred) through dilated pupils in each eye. Grading was performed according to English national grading definitions 12 and quality assured to National Diabetic Eye Screening Programme (NDESP) guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Quality assurance is the key driver for all aspects of the screening programme. A grading classification for England and Wales has been published 3 and a minimum data set for regional and national monitoring developed. 4 Similar developments are underway in Scotland.…”
Section: Introductionmentioning
confidence: 99%